AB0474 The clinical effectiveness and cost savings of tapering biologic dmards in patients with inflammatory arthritis at a uk district general hospital. (12th June 2018) - Lee, W.P.; Manhas, R.; Sebbage, V.; Kyle, S.
Abstract : Background: Biologic DMARDs (bDMARDs) have led to substantial improvement in clinical outcomes for treatment of rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial/peripheral spondyarthropathy(SpA), making remission a realistic target. Current guidelines suggest clinicians should consider tapering after achieving remission in RA. 1 Nevertheless, the optimal approach for tapering bDMARDs remains unknown and un-standardised across conditions. 2 Objectives: To evaluate the tapering strategies on 3 major rheumatological disease entities (RA, PsA, SpA), the number of patients successfully tapered and the total cost saving from successful tapering. Methods: The study was conducted at North Devon District Hospital in Barnstaple, UK and includes all bDMARDs users up until 31st December 2017. The tapering strategy was identified from hospital notes. Patients who are deceased, lost to follow-up or discontinued bDAMRDs due to contraindication or adverse effects were excluded. Successful tapering is defined as patient on tapered dose or had their biologics withdrawn and remains at target treatment level (RA: DAS-28 <2.6; PsA:<3 tender joints and <3 swollen joints; SpA: BASDAI <4). Results: There are a total of 298 patients: 174 RA; 59 PsA; 57 SpA; 8 other diagnoses. 94 patients (31.5%) had attempted tapering: 52 RA, 18 PsA, 22 SpA. 60 (20.1%) successfully tapered their bDMARDs: 34 RA (56.7%); 13 PsA (21.7%); 13 SpA (21.7%). Out of 34 RA, 30 seropositive; 4 seronegative; 24 co-prescribed with synthetic DMARDs, 10 on monotherapy. Out of 13 PsA, 8 co-prescribed with synthetic DMARDs; 5 on monotherapy. 59 tapered by increasing interval of subcutaneous treatment. Only 1 RA patient tapered its IV dose of tocilizumab. This patient is excluded from the final analysis. Tapering of subcut bDAMRDs therapy by disease and price (table 1). Number rounded to 2 decimal points. References: [1] Smolen JS, Landewe R, Breedveld FC, et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update. Ann Rheum Dis2014;73:492–509. [2] Lenert A, Lenert P. Tapering biologics in rheumatoid arthritis: a pragmatic approach for clinical practice. Clin Rheum2017;36:1–8. Disclosure of Interest: None declared ADA – adalimumab; TOC – tocilizumab; ETN – etanercept; GOL – golimumab; CZP – certolizumab pegol Conclusions: In our study, 20% of bDAMRDs users successfully tapered their dose. The total cost saving is significant at £359, 912.98 over the tapered period, of which £249, 321.19 (69%) in RA; £39, 171.01 (11%) in PsA; £71, 420.78 (20%) in SpA.